1952
DOI: 10.1021/jo01139a014
|View full text |Cite
|
Sign up to set email alerts
|

A NEW REACTION OF OLEFINS, NITRILES, AND HALOGENS1

Abstract: A new three-component reaction has been discovered for the synthesis of N-(2-chloroalky1)amides. The synthesis involves interaction of chlorine and an olefin in the presence of a nitrile to give an imide chloride that can be hydrolyzed to an N-(2-~hloroalkyl)amide. This interaction of chlorine, an olefin, and a nitrile has been found to be a general reaction applicable to aromatic and aliphatic nitriles and hydrogen cyanide in combination with such olefins as ethylene, cyclohexene, 1-octene, and styrene. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 8 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Although a previous report has suggested that DBCH is the product of electrochemical bromination in acetonitrile, 6 two independent studies have shown evidence of solvent incorporation when bromine and cyclohexene are homogeneously mixed in specific molar ratios. 5,11 The NMR evidence of the acetamide product, the absence of a third wave (due to DBCH oxidation) and the catalytic increase seen in the second oxidative wave strongly suggests that DBCH is not produced in this system. We have further supported this proposition by using a computer simulation to model the observed voltammetric response, assuming the reaction mechanism given in Scheme 2, and it is to those simulations which we will next turn our attention.…”
Section: Oxidation Of Bromide and Reactivity Of Electrogenerated Brom...mentioning
confidence: 95%
See 2 more Smart Citations
“…Although a previous report has suggested that DBCH is the product of electrochemical bromination in acetonitrile, 6 two independent studies have shown evidence of solvent incorporation when bromine and cyclohexene are homogeneously mixed in specific molar ratios. 5,11 The NMR evidence of the acetamide product, the absence of a third wave (due to DBCH oxidation) and the catalytic increase seen in the second oxidative wave strongly suggests that DBCH is not produced in this system. We have further supported this proposition by using a computer simulation to model the observed voltammetric response, assuming the reaction mechanism given in Scheme 2, and it is to those simulations which we will next turn our attention.…”
Section: Oxidation Of Bromide and Reactivity Of Electrogenerated Brom...mentioning
confidence: 95%
“…The bromination of multiple bonds via electrophillic addition and substitution are well-known reactions and the reactivity of electrogenerated bromine species with a number of organic substrates, including xylene, styrene, phenol, and cyclohexene has been reported in conventional solvents. [5][6][7][8][9][10][11][12][13][14] Herein we report the oxidation of bromide in the roomtemperature ionic liquid, 1-butyl-3-methylimidazolium bis-[(trifluoromethyl)sulfonyl]imide ([C 4 mim][N(Tf) 2 ]) and acetonitrile (MeCN). The subsequent reactivity of the electrogenerated bromine species with cyclohexene is investigated in both solvents and the individual voltammetric responses compared and contrasted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate hydrolysis to the amide was preferable for the alternative case. 103 Higher yields are achieved in the presence of the silver ion (Scheme 30) since the halide ion is removed as the insoluble silver halide, thereby suppressing formation of the vicinal dihalide. 104 Halohydrins also react via the bromonium intermediate in a stereospecific manner.…”
mentioning
confidence: 99%
“…Ring opening of the saccharin ring with potassium ethoxide then gave the chloroamidine ester 5 in 66% overall yield. Formation of 2 is most likely to proceed by ring opening of the initially formed cyclohexene chloronium ion 3 with acetonitrile . The resulting nitrilium ion 4 is then intercepted by the saccharin anion in a classic Ritter-type sequence .…”
mentioning
confidence: 99%